Biblionline Vol. 9, n. 1 (2013) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Biblionline Vol. 9, n. 1 (2013)Link de acesso ao númerohttp://periodicos.ufpb.br/ojs2/index.php/biblio/issue/view/1274/showToc